Pengaruh Strategi Pengelolaan Modal Kerja dan Akses Sumber Pembiayaan terhadap Keberlanjutan Usaha Pedagang Kaki Lima: Studi Kasus di Pulo Jahe, Jakarta Timur - Syah, Seni Nuraenun; Deri Apriadi (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
Street vendors (PKL) are an essential part of the informal sector that significantly contributes to the urban economy, yet they face considerable challenges in sustaining their businesses. This study aims to analyze the influence of working capital management strategies and access to financing on the business sustainability of street vendors in Pulo Jahe, East Jakarta. A quantitative approach was employed using a Likert-scale questionnaire with 33 respondents selected through purposive sampling. Data were analyzed using validity, reliability, normality, multicollinearity tests, and multiple linear regression with t-test and F-test, supported by SPSS version 27. The results indicate that working capital management has a significant effect on business sustainability, while access to financing does not have a significant partial effect. However, both variables simultaneously exert a significant effect on business sustainability. These findings highlight the critical role of working capital management as the primary determinant of sustainability for street vendors, while external financing becomes effective only when supported by adequate financial literacy and managerial capabilities.